Phosphate Phosphors for Solid-State Lighting - Shinde, Kartik N.; Dhoble, S.J.; Swart, H.C.; Park, Kyeongsoon; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The idea for this book arose out of the realization that, although excellent surveys and a phosphor handbook are available, there is no single source covering the area of phosphate based phosphors especially for lamp industry. Moreover, as this field gets only limited attention in most general books on luminescence, there is a clear need for a book in which attention is specifically directed toward this rapidly growing field of solid state lighting and its many applications. This book is aimed at providing a sound introduction to the synthesis and optical characterization of phosphate phosphor for undergraduate and graduate students as well as teachers and researchers. The book provides guidance through the multidisciplinary field of solid state lighting specially phosphate phosphors for beginners, scientists and engineers from universities, research organizations, and especially industry. In order to make it useful for a wide audience, both fundamentals and applications are discussed, together.
Introduction -- Basic Mechanisms of Photoluminescence -- Synthesis of Phosphate Phosphors -- Methods of Measurements (Instrumentation) -- Some Orthophosphate Phosphors -- Some Halophosphate Phosphors -- Some Novel Phosphate Phosphors -- Current Progress in Solid State Lighting.
Keywords: Electric engineering; Optical materials; Materials Science; Optical and Electronic Materials; Solid State Physics; Energy Technology; Energy Efficiency (incl. Buildings).